Kedudukan Hak Pemegang Polis dari Perusahaan Asuransi Jiwa yang Pailit Ditinjau dari Undang-Undang No. 40 Tahun 2014 tentang Perasuransian Undang-Undang No. 37 Tahun 2004 tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang - Sarah Meilinda Putri (UNISBA Press, 2022)
Abstract. The development of increasingly high technology, makes humans produce many goods that can help make it easier for them to carry out their activities. However, in carrying out each activity of course there are some risks that may cause losses such as a car accident, house fire, or theft. Insurance is one of solutions to transfer risks that occur due to unwanted or unexpected events. An insurance company has the goal of providing services to help manage risks that occur through an insurance agreement. However, one of the risks of the insurance company is the occurrence of bankruptcy against the insurance company. Bankruptcy is something that insurance companies and policyholders want to avoid. The purpose of this study is to determine the position of the policyholder of the insurance company that went bankrupt and the legal protection for the policyholder of the bankrupt life insurance company. The method used in this research is a normative juridical method, then the data obtained is processed by descriptive analysis. It is known that the position of the policyholder has not been clearly regulated, but through Law number 40 of 2014 concerning Insurance, the policyholder has the position of a preferred creditor. In addition, it can be seen that legal protection for policyholders from life insurance companies that experience bankruptcy has been regulated in Law number 40 of 2014 concerning Insurance but not specifically regulated but explained in Paragraph 53 that the policy guarantor institution is a protector for policyholders from bankruptcy or liquidation of an insurance companyABTRACT: The development of increasingly high technology, makes humans produce many goods that can help make it easier for them to carry out their activities. However, in carrying out each activity of course there are some risks that may cause losses such as a car accident, house fire, or theft. Insurance is one of solutions to transfer risks that occur due to unwanted or unexpected events. An insurance company has the goal of providing services to help manage risks that occur through an insurance agreement. However, one of the risks of the insurance company is the occurrence of bankruptcy against the insurance company. Bankruptcy is something that insurance companies and policyholders want to avoid. The purpose of this study is to determine the position of the policyholder of the insurance company that went bankrupt and the legal protection for the policyholder of the bankrupt life insurance company. The method used in this research is a normative juridical method, then the data obtained is processed by descriptive analysis. It is known that the position of the policyholder has not been clearly regulated, but through Law number 40 of 2014 concerning Insurance, the policyholder has the position of a preferred creditor. In addition, it can be seen that legal protection for policyholders from life insurance companies that experience bankruptcy has been regulated in Law number 40 of 2014 concerning Insurance but not specifically regulated but explained in Paragraph 53 that the policy guarantor institution is a protector for policyholders from bankruptcy or liquidation of an insurance company. Abstrak. Perkembangan teknologi yang semakin canggih, membuat manusia memproduksi banyak barang yang dapat membantu memudahkan mereka dalam melakukan kegiatan. Namun dalam melakukan setiap kegiatan tentunya memilki resiko yang mungkin menyebabkan kerugian seperti kecelakaan mobil, kebakaran rumah ataupun pencurian. Asuransi merupakan salah satu solusi untuk mengalihkan risiko yang terjadi akibat kejadian yang tidak diinginkan ataupun yang tidak terduga. Suatu perusahaan asuransi memiliki tujuan memberikan layanan jasa untuk membantu mengolah risiko yang terjadi melalui suatu perjanjian asuransi. Akan tetapi salah satu resiko dari perusahaan asuransi adalah terjadinya pailit terhadap perusahaan asuransi tersebut. Kepailitian merupakan hal yang ingin dihindari oleh perusahaan asuransi maupun pemegang polis. Tujuan dari penelitian ini yaitu untuk mengetahui kedudukan pemegang polis dari perusahaan asuransi yang mengalami pailit dan perlindungan hukum bagi pemegang polis dari perusahaan asuransi jiwa yang pailit. Metode yang digunakan dalam penelitian ini adalah metode yuridis normatif, kemudian data yang diperoleh diolah secara analisis deskriptif. Berdasarkan hasil penelitian yang diperoleh, dapat diketahui bahwa kedudukan pemegang polis belum diatur secara jelas, namun melalui Undang-Undang No. 40 Tahun 2014 Tentang Perasuransian, pemegang polis memiliki kedudukan sebagai kreditor preferen. Selain itu, dapat diketahui bahwa perlindungan hukum bagi pemegang polis dari perusahaan asuransi jiwa yang mengalami pailit sudah diatur di dalam UU No. 40 Tahun 2014 Tentang Perasuransian tetapi tidak diatur secara spesifik namun dijelaskan pada Pasal 53 bahwa lembaga penjamin polis merupakan pelindung bagi pemegang polis dari kepailitan atau likuidasi suatu perusahaan asuransi.